Chronic acrolein exposure in Wistar rats: The effects of guarana extracts. (February 2020) - da Silva Bittencourt, Leonardo; Schnorr, Carlos Eduardo; Santos, Daniela Copetti; Rostirolla, Diana Carolina; Moresco, Karla Suzana; Ozório, Pedro; Mingori, Moara Rodrigues; Heinfarth, Luana; Gelain, Daniel Pens; Moreira, José Cláudio Fonseca
Graphical abstract: Highlights: Acrolein (ACR) is an intermediate in the production of many organic materials. ACR induces oxidative stress and exerts a toxic effect on cells. Guarana extracts exhibits beneficial qualities which may attenuate ACR effects. CNS, hepatic toxicity, and behavior in Wistar rats exposed to guarana were examined. Guarana extracts exerted protective effects against ACR induced damage. Abstract: Previous studies have reported that acrolein, may exert harmful effects on the brain. However, information regarding the neuroprotective properties of guarana against acrolein is not available. Due to the lack of research, we initiated the current study to investigate the effects of guarana extracts on acrolein-induced toxicity in the liver and the central nervous system of Wistar Rats. Twelve groups of 60 days old Wistar rats treated with guarana extracts (150, 250, and 350 mg/kg/day) for 8 weeks, were challenged with acrolein (2.5 mg/kg/day). Several parameters associated with oxidative damage to the brain and hepatic function, as well as behavior were evaluated. All tested concentrations of guarana extracts exerted protective effects against acrolein induced damage. No hepatic and oxidative damages or behavioral changes were observed in guarana control groups. To the best of our knowledge, this is the first study of its kind and therefore a milestone in this field.